Influence of Solid Particles on Wellbore Parameters in Solid Fluidization Production Process - Tang, Liang; Liu, Yang (Recent Patents on Mechanical Engineering, 2022)
Objective: To efficiently exploit the hydrate reservoir, based on the problem of a large amount of sand production in the current hydrate reservoir exploration process, combined with the solid fluidization well testing and production method. Methods: A gas-liquid-solid three-phase flow model is established and hydrate decomposition is taken into consideration. The changes in parameters of wellbore pressure, gas volume fraction, liquid volume fraction, temperature and the decomposition rates of wellbore hydrate under the conditions of different rates of sand production are analyzed. Results: The results show that with the increasing rate of sand production during the solid fluidization well testing and production, the pressure of the wellbore is lifted, gas volume fraction declines, liquid volume fraction declines, and the temperature of the wellbore does not change. Moreover, increasing the rate of sand production also leads to the delay of the position where hydrate begins to decompose. Conclusion: With the decrease in hydrate saturation, the pressure of the wellbore goes up, gas volume fraction is lifted, solid volume fraction rises, and decomposition rate of hydrate declines.
Keywords: hydrate decomposition